An introduction to the functioning process of embedded paratext of digital literature: Technoeikon of digital poetry. - Shanmugapriya, T; Menon, Nirmala; Campbell, Andy (Digital Scholarship in the Humanities, 2019)
The recent digital-born electronic literature has heterogeneous components such as kinetic texts, kinetic images, graphical designs, sounds, and videos. These digital components are embedded with the main text as the paratext of print and digital works such as preface, author's name, illustrations, and title. However, the comparative study between paratext and embedded paratext of electronic literature shows the different strategic patterns and functions of these entities. We discuss the conceptual framework of illuminant devices of paratexts and propose a new term technoeikon to recognize the functions of embedded literary artifact in digital literary works. We examine the critical construction of new term technoeikon which has a unique characteristic that makes electronic literary works different from print literature. This essay reviews the cyclical process of technoeikon from the historical perspective of pre-print culture and print culture and acknowledges technoeikon as inherited from our tradition. Due to digital contrivances, technoeikon takes a new expression as performing in digital ecology which is different from our traditional analog. This article presents a case study on Andy Campbell's (2007b) Dim O'Gauble. Also, Campbell responds to the interpretation of new term technoeikon in the fourth section of the essay.